Commentary on Cochrane review of neuraminidase inhibitors for preventing and treating influenza in healthy adults and children. (March 2015) - Jones, M.; Jefferson, T.; Doshi, P.; Del Mar, C.; Heneghan, C.; Onakpoya, I.
Abstract: In recent years there has been much debate and controversy surrounding the efficacy and safety of neuraminidase inhibitors for influenza, in part because the data underlying certain efficacy claims were not available for independent scrutiny. In 2014, a Cochrane review was published, based exclusively on an almost complete set of clinical study reports and other regulatory documents. Clinical study reports can run to thousands of pages, providing an extensive amount of information on the planning, conduct and results of each trial. After a protracted campaign to obtain the reports, the manufacturers of the medications provided them unconditionally. The review authors subsequently published the underlying documents simultaneously with the Cochrane review, endorsing the concept of open science. In the following commentary, the background to and results of this review are summarized and put into clinical context.